1999
DOI: 10.1002/(sici)1097-4636(19991215)47:4<551::aid-jbm12>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Immersion behavior of RF magnetron-assisted sputtered hydroxyapatite/titanium coatings in simulated body fluid

Abstract: The focus of the present study was on the dissolution/degradation behavior of a series of magnetron-sputtered, single-layered HA/Ti coatings on Ti-6Al-4V substrate immersed in SBF. Changes in coating morphology, crystal structure, and adhesion strength with immersion time are characterized. XRD, FTIR, and LVSEM results consistently indicate that highly crystalline monolithic HA coating is very dissolvable in SBF. The monolithic HA coating is largely delaminated in 3 weeks and entirely peeled off the substrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 27 publications
2
31
0
Order By: Relevance
“…Cooley et al [308] investigated the healing rates of bone around titanium implants sputter-coated from an HA target and found that all the thin coatings were lost after 3 weeks of implantation. The monolithic HA and a series of single-layered HA/Ti coatings deposited on Ti-6Al-4V substrates using a RF sputtering system was largely delaminated in 3 weeks after immersion in simulated body fluids [309,310]. In order to decrease the dissolution of the coatings in simulated body fluids, a new biocompatible multi-layered coating was developed by alternately depositing Ti and HA layers on Ti-6Al-4V substrates using radio frequency magnetronassisted sputtering to improve the interfacial properties between the coating and the substrate.…”
Section: Sputteringmentioning
confidence: 99%
“…Cooley et al [308] investigated the healing rates of bone around titanium implants sputter-coated from an HA target and found that all the thin coatings were lost after 3 weeks of implantation. The monolithic HA and a series of single-layered HA/Ti coatings deposited on Ti-6Al-4V substrates using a RF sputtering system was largely delaminated in 3 weeks after immersion in simulated body fluids [309,310]. In order to decrease the dissolution of the coatings in simulated body fluids, a new biocompatible multi-layered coating was developed by alternately depositing Ti and HA layers on Ti-6Al-4V substrates using radio frequency magnetronassisted sputtering to improve the interfacial properties between the coating and the substrate.…”
Section: Sputteringmentioning
confidence: 99%
“…Radiofrequency (RF) magnetron sputtering has been used in wide areas for coatings of thin films with excellent adherence to substrates, 43) and applied to coatings of calcium phosphate films on commercially pure titanium (CP-Ti) 23,37,38,40,44) and þ type titanium alloys. 33,35,36,41,42,45,[47][48][49][50] Ti and its alloys are known as biocompatible metals because of their low elastic modulus, high corrosion resistance and the appropriate combination of strength and ductility. Low processing temperature is also an advantage of RF magnetron sputtering for calcium phosphate coatings for Ti substrates because the mechanical properties of the substrates will be degraded by high processing temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…The sputtering deposition technique has been successfully used to create thin films on titanium surfaces with strong binding 16) . Previous studies have shown how various aspects of the sputtering technique, such as argon gas pressure 35) , voltage 36) , presence of oxygen species 37) , and discharge power level 38) could significantly influence the calcium and phosphate concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Its main advantage is the excellent adhesiveness that can be achieved and its ability to coat onto various types of substrates, including rough surfaces, either by sandblasting or by acid etching. Using this technology, the adhesive strength between a base material and HA has been shown to be >60 MPa 16,17) . In addition, the sputtering technique controls chemical deposition and surface electric charge by adjusting the output voltage and provides the self-assembly of a hybrid surface 4,18) .…”
Section: Introductionmentioning
confidence: 99%